Loss of maturity and homeostatic functions in Tuberous Sclerosis Complex-derived astrocytes - Luinenburg, Mark J.; Scheper, Mirte; Sørensen, Frederik N. F.; Anink, Jasper J.; Van Hecke, Wim; Korshunova, Irina; Jansen, Floor E.; Riney, Kate; van Eijsden, Pieter; Gosselaar, Peter; Mills, James D.; Kalf, Rozemarijn S.; et al. (Frontiers in Cellular Neuroscience, 2023)
Constitutive activation of the mTOR pathway, as observed in Tuberous Sclerosis Complex (TSC), leads to glial dysfunction and subsequent epileptogenesis. Although astrocytes are considered important mediators for synaptic clearance and phagocytosis, little is known on how astrocytes contribute to the epileptogenic network. Herein, we employed single-nuclei RNA sequencing and a hybrid fetal calf serum (FCS)/FCS-free cell culture model to explore the capacity of TSC-derived astrocytes to maintain glutamate homeostasis and clear debris in their environment. We found that TSC astrocytes show reduced maturity on RNA and protein level as well as the inability to clear excess glutamate through the loss of both enzymes and transporters complementary to a reduction of phagocytic capabilities.Our study provides evidence of mechanistic alterations in TSC astrocytes, underscoring the significant impairment of their supportive functions. These insights enhance our understanding of TSC pathophysiology and hold potential implications for future therapeutic interventions.